Macrophage pyroptosis in atherosclerosis: therapeutic potential - Ma Jianying; Wang Yixian; Xu Wenna; Wang Hanjing; Wan Zhengdong; Guo Jiawei (Acta Biochimica et Biophysica Sinica)
Atherosclerosis (AS) is a chronic inflammatory disease characterized by the accumulation of lipid-rich plaques in arterial walls, leading to cardiovascular events such as myocardial infarction and stroke. Macrophage pyroptosis, a form of programmed cell death driven by the NLRP3 inflammasome and caspase-1 activation, plays a critical role in the progression and destabilization of atherosclerotic plaques. This review explores the molecular mechanisms underlying macrophage pyroptosis and their significant contributions to AS pathogenesis. Recent advancements have highlighted the therapeutic potential of targeting key components of the pyroptotic pathway, including the use of nanotechnology to increase drug delivery specificity. These strategies are promising for reducing inflammation, stabilizing plaques, and mitigating the clinical impact of AS. Future studies should focus on translating these findings into clinical applications to develop effective treatments that can halt or reverse AS progression by modulating macrophage pyroptosis.